The Effect of Wildlife Conservation to the Surrounding Community in Nyamagabe District: A Case Study of Nyungwe National Park. - Vestine, Batamuliza (Kabale University, 2019)
A Research Report Submitted in Partial Fulfillment of the Requirement for the award of a Bachelors Degree in Tourism Management of Kabale University